2013
DOI: 10.1021/jp400278t
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Higher Lying Excited States of Cyanine Dyes. An Ultrafast Fluorescence Study

Abstract: The electronic relaxation dynamics of the second singlet excited states of several cyanine dyes was studied through the femtosecond fluorescence up-conversion technique. Our interest in these molecules comes from the potential applications of systems with upper excited singlet states with a long lifetime, which can include electron and energy transfer from the higher lying singlets after one- or two-photon absorption. We studied three series of cyanines with 4-quinolyl, 2-quinolyl, or benzothiazolyl type end g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 67 publications
(131 reference statements)
1
36
0
1
Order By: Relevance
“…For excited state dynamics for one‐ (400 nm) and two‐photon (800 nm) excitation, we used both femtosecond fluorescence up‐conversion and transient absorption spectroscopy. Both instruments are described in detail elsewhere . Briefly, the setups are based on a regenerative amplified Ti : Sapphire laser centered at 800 nm, with a repetition frequency of 1 kHz, temporal width of 180 fs and 0.8 mJ per pulse.…”
Section: Methodsmentioning
confidence: 99%
“…For excited state dynamics for one‐ (400 nm) and two‐photon (800 nm) excitation, we used both femtosecond fluorescence up‐conversion and transient absorption spectroscopy. Both instruments are described in detail elsewhere . Briefly, the setups are based on a regenerative amplified Ti : Sapphire laser centered at 800 nm, with a repetition frequency of 1 kHz, temporal width of 180 fs and 0.8 mJ per pulse.…”
Section: Methodsmentioning
confidence: 99%
“…) or TC5 and 4QC3 (see Ref. ), have 2PA cross‐sections between 100 and 2500 GM. The 850 nm wavelength was chosen to eliminate any contribution from single‐photon excitation since it was verified that linear absorption processes can exist at wavelengths below 820 nm due to tail‐absorption of the first transition.…”
Section: Resultsmentioning
confidence: 99%
“…Also, we recently reported that the second singlet excited state of these systems are atypically long‐lived. This was explained through the energy gap law implying relatively small internal conversion (S 2 →S 1 ) rates of the order of 10 11 s −1 . As stated, the AntOIR system was developed considering the cyanine section as a two‐photon‐absorbing PPG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the lifetime of the excited singlet state is on the order of picoseconds in DTP, photoisomers in carbocyanines can live for microseconds or even milliseconds at room temperature in solution 45 . Probing photoisomerization in femtosecond spectroscopy typically requires significant data analysis of weak but long-lived features 50,51 . In contrast, in I (4) 2D ES the powerful unrestricted terms integrate over the long lifetime, and thus lead to strong spectral features, indicating the presence of photochemical species.…”
Section: Discussionmentioning
confidence: 99%